Sarcastic Expressions in The Simpsons Movie - Punto Padmatantri; Adi Sutrisno (Universitas Gadjah Mada, 2020)
This research identifies the sarcastic utterances found in The Simpsons Movie. It allocates the utterances said by the characters into four categories proposed by Camp (2011): propositional, lexical, like-prefixed, and illocutionary sarcasm. After that, the categorized utterances are identified based on their illocutionary functions by using Leech’s theory (1983): collaborative, convivial, competitive, and conflictive function. The result shows that there are 20 sarcastic utterances found in the movie, 85% of which belongs to illocutionary sarcasm, and the 15% belongs to propositional sarcasm. However, the lexical sarcasm and like-prefixed sarcasm are not used by the characters in expressing sarcasm. Meanwhile, there are only three types of functions that are found in this research; collaborative, conflictive, and convivial. This research also displays evidence that sarcasm is used to protect the speaker from the unwanted consequences that might come from the hearer’s reaction. In addition to context and common ground, the hearer’s response is also necessary to detect an utterance as sarcastic expression.